Imputation of Orofacial Clefting Data Identifies Novel Risk Loci and Sheds Light on the Genetic Background of Cleft Lip ± Cleft Palate and Cleft Palate Only. - Ludwig, Kerstin U.; Böhmer, Anne C.; Bowes, John; Nikolić, Miloš; Ishorst, Nina; Wyatt, Niki; Hammond, Nigel L.; Gölz, Lina; Thieme, Frederic; Barth, Sandra; Schuenke, Hannah; Klamt, Johanna; et al. (2017)
Abstract Nonsyndromic cleft lip with or without cleft palate (nsCL/P) is among the most common human birth defects with multifactorial etiology. Here, we present results from a genome-wide imputation study of nsCL/P in which, after adding replication cohort data, four novel risk loci for nsCL/P are identiﬁed (at chromosomal regions 2p21, 14q22, 15q24 and 19p13). On a systematic level, we show that the association signalswithin this high-density datasetare enriched in functionally-relevant genomic regions that are active in both human neural crest cells (hNCC) and mouse embryonic craniofacial tissue. This enrichment is also detectable in hNCC regions primed for later activity. Using GCTA analyses, we suggest that 30% of the estimated variance in risk for nsCL/P in the European population can be attributed to common variants, with 25.5% contributed to by the 24 risk loci known to date. For each of these, we identify credible SNPs using a Bayesian reﬁnementapproach, with two loci harbouring only one probable causal variant. Finally, we demonstrate that there is no polygenic component of nsCL/P detectable that is shared with nonsyndromic cleft palate only (nsCPO). Our data suggest that, while common variants are strongly contributing to risk for nsCL/P, they do not seem to be involved in nsCPO which might be more often caused by rare deleterious variants. Our study generates novel insights into both nsCL/P and nsCPO etiology and provides a systematic framework for research into craniofacial development and malformation.